New insights into disruption of iron homeostasis by environmental pollutants - Wang, Xiang; Xia, Tian (Journal of environmental sciences (China), 2015)
Among the numerous health conditions environmental pollutants can cause, chronic exposure to pollutants including persistent organic pollutants（POPs） and heavy metals has been shown to disturb a specific biological homeostatic process, the iron metabolism in human body. Disorders of iron metabolism are among the common diseases of humans and encompass a broad spectrum of diseases with different clinical manifestations, ranging from anemia to iron overload, and possibly to neurodegenerative diseases and cancer.Hepcidin–ferroportin（FPN） signaling is one of the key mechanisms responsible for iron supply, utilization, recycling, and storage, and recent studies demonstrated that exposure to environmental pollutants including POPs and heavy metals could lead to disruption of the hepcidin–FPN axis along with disordered systemic iron homeostasis and diseases. This article introduces and highlights the accompanying review article by Drs. Xu and Liu in this journal, which elaborates in detail the adverse effects of environmental pollutants on iron metabolism, and the mechanisms responsible for these toxicological outcomes. It also points out the knowledge gaps still existing in this subject matter. Research that will fill these gaps will improve our understanding of the issue and provide useful information to prevent or treat diseases induced by environmental pollutants.